The Quandary of Contemporary Pagan Archives - Reese, Garth (Pomegranate, 2007)
Although religious archives as they exist today are a relatively recent development, the need to maintain a collection of materials essential to the administration of a church or other religious body emerges at the moment that body is founded/ This is especially true in the case of contemporary Pagan religious bodies, many of which, whether because they tend to be non-scriptural, or because they are smaller, younger, or less secure than mainline Christian denominations, have neither created nor maintain formal archives. ‘Archival’ materials related to these bodies tend to reside on hard drives or in file cabinets in members’ homes or offices; hardly a dependable setting for long-term preservation. Yet archives are essential to gaining credibility and respectability in the greater American (even global) religious landscape. More importantly, they allow religious bodies to retain control over their own histories, which is essential for small, sometimes threatened, groups like contemporary Pagans.